Loss of expression of TGF-βs and their receptors in chronic skin lesions induced by sulfur mustard as compared with chronic contact dermatitis patients - Khaheshi, Isa; Keshavarz, Saeed; Imani Fooladi, Abbas Ali; Ebrahimi, Majid; Yazdani, Samaneh; Panahi, Yunes; Shohrati, Majid; Nourani, Mohammad Reza (BMC dermatology, 2011)
Sulfur mustard (SM) is a blister-forming agent that has been used as a chemical weapon. Sulfur mustard can cause damage in various organs, especially the skin, respiratory system, and eyes. Generally, the multiple complications of mustard gas result from its alkalizing potency; it reacts with cellular components like DNA, RNA, proteins, and lipid membranes.TGF-β is a multi-functional cytokine with multiple biological effects ranging from cell differentiation and growth inhibition to extracellular matrix stimulation, immunosuppression, and immunomodulation. TGF-β has 3 isoforms (TGF-β 1, 2, 3) and its signaling is mediated by its receptors: R1, R2 and intracellular Smads molecules.TGF-β has been shown to have anti-inflammatory effects. TGF-βs and their receptors also have an important role in modulation of skin inflammation, proliferation of epidermal cells, and wound healing, and they have been implicated in different types of skin inflammatory disorders. Seventeen exposed SM individuals (48.47 ± 9.3 years), 17 chronic dermatitis patients (46.52 ± 14.6 years), and 5 normal controls (44.00 ± 14.6 years) were enrolled in this study.Evaluation of TGF-βs and their receptors expressions was performed by semiquantitative RT-PCR. Only TGF1 was analyzed immunohistochemically. Our results showed significant decreases in the expression percentages of TGF-β 1, 2 and R1, R2 in chemical victims in comparison with chronic dermatitis and normal subjects and significant decreases in the intensity of R1 and R2 expressions in chemical victims in comparison with chronic dermatitis and normal controls. (P value < 0.05) TGF-βs and their receptors appear to have a noticeable role in chronic inflammatory skin lesions caused by sulfur mustard.